Physicochemical characterization and In vitro anti-cancer effects of iron-manganese and iron-doped sulfated zirconia nanoparticles in cancer cell lines - Khlaif, Mohamed Qasim (2016)
Crystal nanoparticle is a new system with potential as a therapeutic agent in the treatment of diseases. The objectives of this study are to synthesize, characterize and determine the anticancer cell effects of iron-manganese and iron-doped sulfated zirconia nanoparticles. In this study the iron-manganese- and iron-doped sulfated zirconia nanoparticles were prepared by hydrothermal impregnation method followed by calcination. The characterization of both nanoparticles were carried out using X-ray diffraction (XRD), thermal gravimetric analysis (TGA), fourier transform infrared spectroscopy (FT-IR), Brunner-Emmett-Teller (BET) surface area measurements, Xray fluorescence (XRF), X-ray photoelectron spectroscopy, zeta potential (ZSP) measurement, and transmission electron microscopy (TEM). The cytotoxicity of the nanoparticles was determined via the 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide assay on human breast adenocarcinoma (MDA-MB-231), colorectal adenocarcinoma (HT29), and hepatocellular carcinoma (HepG2) cell lines, and two normal human cell lines, the Chang liver and human umbilical vein endothelial cells (HUVEC) cell lines. The results showed that the iron-manganese- and iron-doped sulfated zirconia nanoparticles were of average size 12.7 and 32.0 nm, respectively and zeta potential of 15.0 and 0.206 mV, respectively. These nanoparticles tend to aggregate in solution. The iron-manganese- and iron-doped sulfated zirconia nanoparticles are highly toxic to the MDA-MB-231 and HepG2 cells, respectively, showing dramatic morphological changes suggesting loss of cell viability. The nanoparticles are comparatively less toxic to the HT29 cells compared to the other cancer cell lines. The study suggests that the anticancer effects of iron-manganese- and iron-doped sulfated zirconia nanoparticles implicate caspase-3, 8 and -9 in their anticancer cells activities. The findings from the study highlight the potential of ironmanganese- and iron-doped sulfated zirconia nanoparticles as therapeutic agents in the treatment of cancers, while showing lesser effect on normal cells.